2009
DOI: 10.3390/molecules14020655
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of N-(Arylcarbamothioyl)-cyclohexanecarboxamide Derivatives: The Crystal Structure of N-(Naphthalen-1-ylcarbamothioyl)cyclohexanecarboxamide

Abstract: A number of N-(arylcarbamothioyl)cyclohexanecarboxamide derivatives (aryl substituents: phenyl, 2-chlorophenyl, 3-chlorophenyl, 4-chlorophenyl, o-tolyl, p-tolyl, 3-methoxyphenyl, 4-methoxyphenyl and naphthalen-1yl) have been synthesized. The compounds obtained were characterized by elemental analyses, IR spectroscopy and 1H-NMR spectroscopy. N-(naphthalen-1-ylcarbamothioyl)cyclohexanecarboxamide, H2L9, was also characterized by a single crystal X-ray diffraction study. This compound, C18H20N2OS, crystallizes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 40 publications
3
32
0
Order By: Relevance
“…It was reported that the antimicrobial activity is related to the cell wall structure of the bacteria because the latter is essential to the survival of bacteria. Gram positive bacteria possess a thick cell wall containing many layers of peptidoglycan and teichoic acid, but in contrast, gram negative bacteria have a relatively thin cell wall consisting of few layers of peptidoglycan [24]. This difference in cell wall structure can produce differences in antibacterial susceptibility and some antibiotics can kill only gram positive (or gram negative) bacteria and is ineffective against the other type.…”
Section: Biological Activitymentioning
confidence: 99%
“…It was reported that the antimicrobial activity is related to the cell wall structure of the bacteria because the latter is essential to the survival of bacteria. Gram positive bacteria possess a thick cell wall containing many layers of peptidoglycan and teichoic acid, but in contrast, gram negative bacteria have a relatively thin cell wall consisting of few layers of peptidoglycan [24]. This difference in cell wall structure can produce differences in antibacterial susceptibility and some antibiotics can kill only gram positive (or gram negative) bacteria and is ineffective against the other type.…”
Section: Biological Activitymentioning
confidence: 99%
“…Moreover, the heterocyclic Schiff bases having the different functional group to interact with nucleoside bases with greater tendency even after complexation with metal ions. The enhancement microbial activity of the metal complexes may be occurring on the basis of Overtone's concept and Tweedy's Chelation theory [30,31]. According to these theories, in a metal complex, the coordination reduces the polarity of metal ion because the partially sharing of positive charge of the metal with donor atoms of the ligand within the chelating ring system.…”
Section: X-ray Diffraction:-mentioning
confidence: 99%
“…The 1 H NMR spectra were recorded on a Varian VXR-300 (300 MHz, for HL 1 , HL 2 , complexes 1-4) and a Bruker Advance DRX-500 spectrometer (500.13 MHz for HL 3 , HL 4 , complexes 5, 6) in DMSO-d 6 solution using TMS as an internal standard. The PdCl 2 (Pd content 59%, Merck) was used as the starting metal salt.…”
Section: Experimental Partmentioning
confidence: 99%
“…Thiourea and its N-substituted derivatives are efficient complexing agents for metal ions, which are widely used as ligands in coordination chemistry [1][2][3]. The presence of unshared electron pairs in the sulphur atom and two nitrogen atoms allows to form the complex compounds with transition metal salts of the different type, many of which possess valuable applied properties (optical, semiconductor, biological, etc.)…”
mentioning
confidence: 99%